Multiple myeloma complicated with pseudomonas endocartiditis - Todaro,Juliana (2012)
Patients diagnosed with multiple myeloma are more susceptible to infections which are the major causes of morbidity and mortality associated to this disease. The main infectious agents involved are Gram-positive bacteria. However, after chemotherapy an increase in the incidence of Gram-negative strains is observed. These bacteria are also responsible for most cases of urinary tract infections. Here is reported a rare case in a 73-year-old man with multiple myeloma who developed endocarditis due to pseudomonas.